2011
DOI: 10.1177/0021998311412988
|View full text |Cite
|
Sign up to set email alerts
|

On the in-plane deformability of cross-plied unidirectional prepreg

Abstract: PostprintThis is the accepted version of a paper published in Journal of composite materials. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination. AbstractThe work presented herein aims to investigate the in-plane properties of cross-plied unidirectional prepreg using the bias extension method. The study is focusing on different generations of carbon fibre/epoxy material systems and testing is performed at elevated temperatures to enhance formabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 12 publications
(40 reference statements)
4
39
0
Order By: Relevance
“…This work aims to characterise the interply friction for four different non-bleeding, thermoset prepreg materials, for which initial tests in the workshop have indicated a more complex behaviour than purely hydrodynamic. In an earlier study [2] it was seen that although having seemingly similar characteristics (i.e. comparable type of fibres, matrix, fibre volume fraction, etc), the materials have shown significantly different interply friction.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This work aims to characterise the interply friction for four different non-bleeding, thermoset prepreg materials, for which initial tests in the workshop have indicated a more complex behaviour than purely hydrodynamic. In an earlier study [2] it was seen that although having seemingly similar characteristics (i.e. comparable type of fibres, matrix, fibre volume fraction, etc), the materials have shown significantly different interply friction.…”
Section: Introductionmentioning
confidence: 99%
“…This is done by forcing the different layers to deform by intraply deformation (within the prepreg ply) and interply deformation (in-between the prepreg plies); both in the plane and due to bending of the fibres out of the plane. While previous studies [1,2] have shown large differences in the in-plane deformation behaviour in general (between different generations of prepreg materials), this paper focuses only on the in-plane interply deformation, or more exactly the resistance to interply deformation, by measuring the friction in-between separate prepreg plies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During in-plane shear the fibres reorient to conform to the shape of the tool, which is often seen as the most important measure when it comes to forming. For weaves, a limit of in-plane shear deformation is often defined as the shear locking angle, although this does not seem to exist in the same way for cross-plied UD prepreg [11,16,17].…”
mentioning
confidence: 99%